(untitled) (Italian Review of Legal History, 2019)
This essay intends to analyze the first intervention of the Italian State, in private bargaining and in the practice of relations between employers and workers, implemented with law 11 February 1886, no. 3657 for the protection of work and child exploitation. Soon after the national unification, the economic structure of Italy appeared, compared to other European nations, still of a pre-industrial type, and characterized by few attempts to move from craftsmanship to industry in certain sectors and only in the regions of north. The conditions of the backwardness of Italian industry, certainly not very sensitive to the need for technical updating, forced the employers, that mast operate in a highly competitive and unsecured market against foreign goods, to which no form was foreseen of protection, to exploit the simplest conditions beyond all limits, or to be more precise the low labor costs and the absence of legal protection. From here a great deal of child (together with the women: so-called half forces) in the production process and used in heavy, harmful and unhygienic works, with practically deleterious effects from the health point of view for their already so weak physical conditions, between the indifference of employers driven mainly by their capitalist interests to exploit them without any legal constraint, and the increasingly urgent need to protect this labor force.